Desenvolvimento de uma biblioteca didática para acesso aos componentes da Spartan-3E Starter Kit Board - Ribeiro, Julio Cesar de Paiva (2017)
The university has many ways of supporting the teachings passed on to the students and this makes all the difference in how they will take possession of this knowledge. Books, handouts, simulations, development kits all come to a more solid learning, which guarantees the student to retain the contents and improve them. This paper presents the development of a library using the VHDL language for access to components of the Spartan-3E Starter Kit Board. The research methodology adopted in the development of this work was that of experimental development that is characterized by the creative work carried out in a systematic way. The developed library contains the following components: rotary encoder, LCD display, PS/2 port, A/D and D/A converters. The implemented components were modeled to be used in the design methodology through a schematic diagram, allowing the user to perform applications such as analog to digital or digital to analog conversion. For the use of the implemented components, only the knowledge about circuits and digital systems is necessary, which makes the Spartan-3E Starter Kit Board a more didactic tool. In addition to the implemented components, a documentation was created that contains technical information about the components developed and a tutorial on using the library.